Comparison of iFR and FFR for coronary physiology evaluation in patients with severe aortic stenosis. (25th November 2020) - Kleczynski, P; Dziewierz, A; Rzeszutko, L; Dudek, D; Legutko, J
Abstract: Background: Reliable coronary physiology assessment with pressure derived indexes in patients with aortic stenosis (AS) rises problems due to its complex nature. Recent data suggest that fractional flow reserve (FFR) may underestimate intermediate coronary stenosis in a presence of AS whereas instantaneous wave-free ratio (iFR) values may remain similar after treatment of AS. Furthermore, both indices has not been validated yet in AS. Aim: We aimed to find a thresholds for coronary ischemia in the setting of aortic Material and methods: The functional significance of 416 coronary lesions was investigated with iFR and FFR measurements in 221 AS patients. The iFR-FFR diagnostic agreement has been tested using the cut-off value for iFR of 0.89. Results: Mean value of %DS was 58.6±13.4%, FFR was 0.85±0.07 and iFR – 0.90±0.04. FFR ≤0.80 was measured in 26.0% of interrogated vessels, iFR ≤0.89 – in 33.2%. The correlation between iFR and FFR was good (r=0.83, p<0.001) and with good agreement between iFR and FFR (mean difference −0.0059, 95% CI −0.056–0.062). The AUC at ROC curve analysis for iFR ≤0.89 was 0, 997 (0, 986 to 1, 000, p<0.001) for FFR. According to ROC analysis, the best FFR cut-off in predicting iFR ≤0.89 was ≤0.82 (J=0.96). The diagnostic accuracy for identifying iFR ≤0.89 was 97.7% for FFR. Conclusion: In the presence of AS, FFR had good agreement with iFR values. However, FFR threshold for predicting iFR below 0.89 may be different from a standard threshold and that should be taken into account while assessing coronary physiology in the setting of AS. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Science Center